ChemInform Abstract: anti‐Markovnikov Hydroheteroarylation of Unactivated Alkenes with Indoles, Pyrroles, Benzofurans, and Furans Catalyzed by a Nickel—N‐Heterocyclic Carbene System. Issue 9 (February 2016) - Schramm, York; Takeuchi, Makoto; Semba, Kazuhiko; Nakao, Yoshiaki; Hartwig, John F.
Abstract: The catalytic addition of C—H bonds at the C‐2 position of heteroarenes, such as pyrroles, indoles, benzofurans, and furans, is investigated.